Творчість Трумена Капоте в 1940–1950 рр.: біографічний контекст - Чирва, Юлія Олександрівна; Chyrva Yu. (СНУ ім. Лесі Українки, 2013)
У статті висвітлено основні етапи життя та ранньої творчості (40–50-ті рр.) Трумена Капоте. У ранніх творах письменника простежується абсолютно сформований індивідуально-авторський стиль і чітко окреслюється художня картина світу, спроектована на особливості авторського сприйняття дійсності. The article deals with the early work (40–50th) of the American writer Truman Capote in the biographical context. It is determined with the fact that the writer’s early works are autobiographical. Capote showed the vivid picture of the life of the American society: the author was interested in the problems of family, upbringing, morals, good and evil. The author draws attention to the people’s inner life. Their social status, views, rules of conduct, psychology are quite different. They are persons with individual characters whose behavior is determined by the real social contradiction. The author concentrates on the spiritual aspects of the person’s being. T. Capote deepens in the indefinite feelings, in the striving for another life, dreams, hope, premonition, belief in something mysterious. The interpretation of the American writer’s early works lets us investigate Capote’s artistic world and the evolution of the changes of his work deeper.
Truman Capote’s Work in the 1940–1950 in the Authobiographical Context
Keywords: Трумен Капоте; рання творчість; ліричність; психологізм; «Other Voices, Other Rooms»; «The Grass Harp»; «Breakfast at Tiffany’s»; Truman Capote; early works; lyric; psychologism; «Other Voices, Other Rooms»; «The Grass Harp»; «Breakfast at Tiffany’s»